Climatic Events and Natural Disasters of 21st Century: A Perspective of Pakistan: Climatic Events and Natural Disasters of 21st Century: A Perspective of Pakistan - Umer Aslam, Hafiz Muhammad; Asif Butt, Aisha; Shabbir, Humera; Javed, Mohsin; Hussain, Shabbir; Nadeem, Sohail; Raza, Hamid; Harron, Shah Muhammad; Arshad, Sidra (International Journal of Economic and Environmental Geology, 2024)
In recent years, the frequent occurrence of natural calamities in the world has gained much attention due to infrastructure and life losses. Increase in global temperature has threatened the earth’s climate, causing unpredictable and extreme weather events more often. These events were both short-term as well as long-term. In spite of insufficient monitoring coverage of inner areas and high altitudes, an intensification of average yearly temperature has been observed after the 20th century in many regions of Asia. Pakistan has faced a number of natural disasters including severe floods, devastating earthquakes, disturbing droughts, distressing smog, extreme temperature and torrential rainfall patterns. These calamities have affected people economically, socially, physically and mentally by posing a threat to earth, its species and their livelihood. This paper was aimed to document the natural calamities in Pakistan since the beginning of 21st century till date. The country is facing the problem of intense and longer summers and has witnessed two intense heat waves. Moreover, in some areas, extensive droughts are threatening crops, freshwater supply and wildlife. In recent years, the problem of smog has emerged in Pakistan, especially in Punjab. The problem is getting worse in every coming year due to overpopulation, cities expansion, increased emission of greenhouse gases, open burning of crop residues and extreme reliance on fossil fuels for energy purpose. So far in this century, Pakistan has faced 3 droughts, 2 heat waves, 10 severe floods, 27 major earthquakes, 2 consecutive sessions of severe smog and extreme high and low temperature events. Some of the deadliest events were; 2005 Kashmir earthquake claiming 87,350 human lives and 2010 flood impacting nearly 20 million people with 1,781 causalities. Change in climate is posing a severe threat to species, livelihood of the human beings and the earth. Global warming is causing warming of oceans and consequently rise in sea level. Climate change affects average as well as extreme temperatures hence increasing the probability climate-related disasters. Thus, global warming is causing a chain of catastrophic events that make the problem even more complex to understand.